Estudio de factibilidad para la creación de una empresa de alquiler de maquinaria pesada usada para el sector construcción en la ciudad de Pereira, Risaralda (2013)
Without any doubt, the construction sector is one of the most important economic sectors within their regions in Colombia and productive areas. This sector is considered of great importance not only for the ability to generate employment within regions and constant link presents a number of immersed in it companies, but by the high capacity of stimulating demand for an amount of raw material development activity. Following the above, in the town of Pereira manufacturing industry is considered one of the most important activities in the economic development of the municipality, which has concentrated its efforts in the last two years in the construction of buildings of Affordable Housing (VIS) according to the DANE in its report of May 2013, showing their license numbers a cumulative variation of 106.89 % for travel from January to May 2013. Overall implementation of raw material in skilled labor, unskilled, machinery (heavy and not heavy ) and other inputs, is vital for the development of the construction sector for the year , given that thinking in productivity and efficiency in this sector is of interest to construction firms of licensed projects for the coming years , as they will think of maximizing their performance in order to achieve a higher profit for the company, is in this way that this paper aims to assess the feasibility or feasibility of creating a company that is in charge of renting heavy equipment and machinery (imported) in the town of Pereira , that for the purpose of providing these tools companies both technical and updated to allow them to maximize their production, reducing time deliveries being more efficient. In this issue you will find in Chapter 1 with regard to the methodological part, performing a brief summary and overview of the economic activity that is to enter, in Chapter 2 you will find an overview of the project feasibility where records are described and related to the target market with respect to market research (Chapter 3) a deeper and detailed sector analysis is performed to distinguish which factors are crucial in order to exercise the service in the technical study and engineering (chapter 4) is provided space and equipment required for the implementation of economic activity to which they will devote the company, the legal study (chapter 5) mainly part of the legal framework which is based on rules, regulations and laws set by the state , administrative study (chapter 6) in this company objectives are reflected and the way in which routed each of the parties to achieve the goal , environmental study (chapter 7) refers to the regulation and care which should govern the company to mitigate the environmental impact, financial study (Chapter 8) summarizes the financial statements are prepared and presented in accordance with the rules and principles of accounting according to the decree 2643 of 1993.